Enhancing maize resilience through bundled climate-smart solutions across Agricultural Commercialization Clusters (ACCs) in Ethiopia: From pilot implementation to scalable impact - Dejene, Sintayehu W.; Alemayehu, Sintayehu; Tadesse, Terefe; Tesfaye, Lidya; Gebre, Liyuneh; Tegegne, Getachew; Chilambe, Pedro; Girvetz, Evan (2025)
Maize production in Southern Ethiopia faces major challenges from climate variability, including erratic rainfall, heat stress, and pest outbreaks, which constrain yields and threaten smallholder livelihoods. To address these challenges, the CGIAR Program on Scaling for Impact (SfI) piloted a bundled Climate-Smart Solutions (3S) package integrating climate risk profiling, context-specific CSA practices, access to finance, weather and climate information services (WCIS) and agro-advisory support, and capacity-building interventions. Climate risk profiling assessed historical and contemporary data on rainfall variability, temperature trends, drought, waterlogging, and extreme events, generating location-specific profiles that guided farm-level and policy decisions. Based on these profiles, best-bet CSA practices were co-identified and implemented, including improved maize varieties, intercropping, mulching, cover cropping, crop rotation, integrated soil fertility management, agroforestry, and integrated pest management, with gender- and zone-specific adaptations. Adoption was supported through a Climate-Smart Credit Scoring (CSCS) Tool, enabling 6,000 farmers to be profiled, 1,800 shortlisted for finance, and 600 to access credit and insurance, facilitating timely input use, enhanced CSA adoption, and strengthened resilience to climatic and economic shocks. Weather and climate information services and agro-advisory support provided actionable guidance on planting, pest management, and input use, combining forecasts with local knowledge. Observations confirmed improvements in germination, seedling vigor, vegetative growth, cob formation, and pest management, translating into higher productivity and strengthened resilience. The bundled 3S solution demonstrates substantial scaling potential across maize-producing ACCs, other strategic crops, and mixed crop–livestock systems. Integration of digital platforms, public-private partnerships, and capacity-building frameworks ensures effective delivery, sustainability, and broad impact, offering a replicable model for climate-resilient agricultural development, food security, and improved livelihoods in Ethiopia.